Penguatan Kapasitas Kinerja Guru di SD Muhammadiyah 3 Tegal - Devi Nur Utami (Fakultas Ilmu Tarbiyah dan Keguruan, Institut Agama Islam Bakti Negara Tegal, 2022)
The purpose of this research was first to find out how the concept of morning briefing habituation in strengthening the capacity of teacher performance. Second, how is the performance capacity of teachers at SD Muhammadiyah 3 Tegal? Third, to find out how the implementation of morning briefing in strengthening the performance capacity of teachers at SD Muhammadiyah 3 Tegal. The method used in this research is qualitative research with descriptive research approach. The results showed that the implementation of morning briefing activities could strengthen the performance capacity of teachers at SD Muhammadiyah 3 Tegal. It can be seen that with the morning briefing activities, the performance capacity of teachers has increased. There are no more teachers who are often late, work based on the vision and mission of the school, and can synergize with others. The benefits of the implementation of morning briefing activities on the performance of Muhammadiyah 3 Tegal Elementary School teachers are teachers with this morning briefing activity teachers can evaluate their performance that has been done before to be better in the future.